2010
DOI: 10.1603/en10013
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Aethina tumida (Coleoptera: Nitidulidae) With Baited Bottom Board Traps: Occurrence and Seasonal Abundance in Honey Bee Colonies in Kenya

Abstract: The population dynamics of the honey bee pest Aethina tumida Murray (small hive beetle) have been studied in the United States with flight and Langstroth hive bottom board traps baited with pollen dough inoculated with a yeast Kodamaea ohmeri associated with the beetle. However, little is known about the population dynamics of the beetle in its native host range. Similarly baited Langstroth hive bottom board traps were used to monitor the occurrence and seasonal abundance of the beetle in honey bee colonies at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Entomopathogenic fungi (Muerrle et al 2006) and entomopathogenic nematodes (Ellis et al 2010) are major biological control agents found attacking the SHB (Cuthbertson et al 2012). Besides, there are some minor agents including Aspergillus niger and A. flavus (Richards et al 2005), the storage mite Caloglyphus hughesi (Strauss et al 2010), the ant Pheidole megacephala, as a predator of larvae (Torto et al 2010), and a protozoan pathogen (Wright and Steinkraus 2013) have been reported. Mortality of SHB increased when B. bassiana and M. anisopliae variety anisopliae were used, using spore suspension bioassays.…”
Section: Biocontrol Agentsmentioning
confidence: 99%
“…Entomopathogenic fungi (Muerrle et al 2006) and entomopathogenic nematodes (Ellis et al 2010) are major biological control agents found attacking the SHB (Cuthbertson et al 2012). Besides, there are some minor agents including Aspergillus niger and A. flavus (Richards et al 2005), the storage mite Caloglyphus hughesi (Strauss et al 2010), the ant Pheidole megacephala, as a predator of larvae (Torto et al 2010), and a protozoan pathogen (Wright and Steinkraus 2013) have been reported. Mortality of SHB increased when B. bassiana and M. anisopliae variety anisopliae were used, using spore suspension bioassays.…”
Section: Biocontrol Agentsmentioning
confidence: 99%
“…Interestingly, the numbers of SHB larvae in colonies were significantly larger than the numbers of adults. Therefore, losses as a result of the hosts (Neumann & Härtel, ), natural enemies (Torto et al ., ) or unfavourable conditions for pupation (Neumann et al ., ) could possibly be compensated for. In conclusion, it appears as if the observed low‐level reproduction can be sufficient to explain local infestation levels of African honeybee colonies with adult SHBs irrespective of any other reproductive options (Neumann et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Even though ants can drive an entire honeybee colony out of their hive (Fell 1997) and P. megacephala is known to be a predator of SHB larvae (Torto et al 2010), there were no significant effect of ant presences on either SHB or GWM reproduction. Since SHB larvae are often covered with a slimy coating derived from fermenting honey (Neumann and Härtel 2004), this coating may protect them against ant predation as long as some honey is left behind in the nests.…”
Section: Discussionmentioning
confidence: 99%